The effect of advanced secondary municipal wastewater treatment on the molecular composition of dissolved organic matter - Maizel, Andrew C. (Water Res, 2017)
There is a growing interest in water reuse and in recovery of nutrients from wastewater. Because many advanced treatment processes are designed to remove organic matter, a better understanding of the composition of dissolved organic matter (DOM) in wastewater is needed. To that end, we assessed DOM in the Nine Springs Wastewater Treatment Plant in Madison, Wisconsin by UV–visible spectroscopy and Fourier transform-ion cyclotron resonance mass spectrometry. Samples were collected from the influent and effluent of two different secondary treatment processes and their respective secondary clarifiers, the UV disinfection unit, and an Ostara treatment system, which produces struvite via chemical precipitation. The optical properties reveal that DOM throughout the plant is relatively aliphatic and is low in molecular weight compared to DOM in freshwater systems. Furthermore, the DOM is rich in heteroatoms (e.g., N, S, P, and Cl) and its molecular formulas are present in the lipid-, protein-, carbohydrate-, and lignin-like regions of van Krevelen diagrams. Secondary treatment produces DOM that is more aromatic and more complex, as shown by the loss of highly saturated formulas and the increase in the number of CHO, CHON, and CHOP formulas. The two secondary treatment processes produce DOM with distinct molecular compositions, while the secondary clarifiers and UV disinfection unit result in minimal changes in DOM composition. The Ostara process decreases the molecular weight of DOM, but does not otherwise alter its composition. The optical properties agree with trends in the molecular composition of DOM within the main treatment train of the Nine Springs plant.